Low-cost COTS GNSS interference monitoring, detection, and classification system - van der Merwe, Johannes; Contreras Franco, David; Hansen, Jonathan; Brieger, Tobias; Feigl, Tobias; Ott, Felix; Dorsaf, Jdidi; Ruegamer, Alexander; Felber, Wolfgang (Sensors, 2023)
Interference signals cause position errors and outages to global navigation satellite system (GNSS) receivers. However, to solve these problems, the interference source must be detected, classified, its purpose determined, and localized to eliminate it. Several interference monitoring solutions exist, but these are expensive, resulting in fewer nodes that may miss spatially sparse interference signals. This article introduces a low-cost commercial-off-the-shelf (COTS) GNSS interference monitoring, detection, and classification receiver. It employs machine learning (ML) on tailored signal pre-processing of the raw signal samples and GNSS measurements to facilitate a generalized, high-performance architecture that does not require human-in-the-loop (HIL) calibration. Therefore, the low-cost receivers with high performance can justify significantly more receivers being deployed, resulting in a significantly higher probability of intercept (POI). The architecture of the monitoring system is described in detail in this article, including an analysis of the energy consumption and optimization. Controlled interference scenarios demonstrate detection and classification capabilities exceeding conventional approaches. The ML results show that accurate and reliable detection and classification are possible with COTS hardware.<br
Keywords: global navigation satellite system (GNSS); interference; detection; classification; machine learning; commercial-off-the-shelf (COTS)